EFFICACY OF CARDIOPROTECTOR TREATMENT OF DECOMPENSATED HEART FAILURE IN PATIENTS WHO HAVE TRANSFERRED ACUTE MYOCARDIAL INFARCTION IN FOCUS - Levandowska, K. V.; Naluzhna, T. V.; Merhel, T. V.; Yusypchuk, U. V.; Gridzhuk, T. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2022)
In Ukraine, as well as in Europe and America, chronic heart failure (CHF) remains one of the most pressing problems of cardiology. This diseaseremains a leading factor in development adverse cardiovascular events and reduces the quality of life those patients whohad myocardial infarction. Endothelial dysfunction is a one of the main links in the formation of decompensated heart failure (HF) during the postinfarction period. An alternative direction in its treatment is cytoprotectionthat is characterized by the use of hemodynamically neutral drugs. Such drugs are energy substrate and have the properties of formation and storage of macroergic compounds in cardiomyocytes [2].